2023
DOI: 10.3389/fimmu.2023.1269896
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NAD+ metabolism: dual roles in cancer treatment

Jiaxin Yong,
Songqing Cai,
Zhaolei Zeng

Abstract: Nicotinamide adenine dinucleotide (NAD+) is indispensable for various oxidation-reduction reactions in mammalian cells, particularly during energy production. Malignant cells increase the expression levels of NAD+ biosynthesis enzymes for rapid proliferation and biomass production. Furthermore, mounting proof has indicated that NAD-degrading enzymes (NADases) play a role in creating the immunosuppressive tumor microenvironment (TME). Interestingly, both inhibiting NAD+ synthesis and targeting NADase have posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 176 publications
0
1
0
Order By: Relevance
“…Studies have shown that cancer cells, known for high glycolysis levels, produce large amounts of NAD+ ( Yong, Cai & Zeng, 2023 ). NAD+ is crucial in energy metabolism and important cellular signaling processes like mono-ADP and poly-ADP ribosylation, as well as NAD+-dependent protein deacetylation ( Diefenbach & Burkle, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cancer cells, known for high glycolysis levels, produce large amounts of NAD+ ( Yong, Cai & Zeng, 2023 ). NAD+ is crucial in energy metabolism and important cellular signaling processes like mono-ADP and poly-ADP ribosylation, as well as NAD+-dependent protein deacetylation ( Diefenbach & Burkle, 2005 ).…”
Section: Discussionmentioning
confidence: 99%